(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
A new South-east en Ukraine a species of moss Aulacomnium palustre (Hedw.) Schwaegr. is found. Anatomic and morphological character of this species are carefully investigated in the three populations. Index of variation and index of correlation are calculated. Possible ways of migrating Aulacomnium palustre to the Donetsk region are discussed.